Compliance of RTE in Elementary Education Through SSA: An Assessment in Case of Uttar Pradesh. - Tyagi, R.C. and Siddiqui, Tarannum (2014)
RTE Act confers the right to free and compulsory education to children between 6 and 14 years of age. No child shall be retained in the same class or made to sit in the Board Examination till the completion of elementary education. In case a child above 6 years of age has not been admitted into any school or primary education of the child is not completed after admission, such a child shall be admitted into a class that suits his/her age. A child so admitted shall undergo special training for a definite period to come up to the level of others in that class. Such a child shall continue to receive primary education even if the age of the child crosses the fourteen year limit. This paper is based on concurrent monitoring of Sarva Shiksha Abhiyan (SSA) which is running all over the country. Special focus of this paper is to assess the efforts to compliance of RTE in elementary education through SSA in four districts of UP.